Novel mutation of MAP3K1 gene in 46,XY DSD with complete gonadal dysgenesis - Pei-Hsiu Yu; Meng-Che Tsai; Chun-Ting Chiang; Han-Yu Wang; Pao-Lin Kuo (Elsevier, 2022)
Objective: Swyer syndrome, or 46, XY complete gonadal dysgenesis, is a disorder of human sexual development which present with female external genitalia, lack of female reproductive organs, and a 46, XY karyotype. Many genes that participate in human sexual development have been implicated in the pathogenesis of 46, XY gonadal dysgenesis. Case report: A 18-year-old phenotypically female was presented with primary amenorrhea. Surveillance revealed hypergonadotropic hypogonadism, a normal male 46, XY karyotype and absent of functional gonad, which was confirmed by pathological examination of the streak gonad. Whole exome sequencing showed germline mutations of a novel missense variant, c.570G > C, p.Lys190Asn, in exon 2 of MAP3K1 gene. Conclusion: Given evolutionary conservation of lysine residue at position 190, the amino acid substitution may interfere with interaction between MAP3K1 and RHOA, and contributes to complete gonadal dysgenesis in the context of 46,XY.